Sturla Þórðarson skald, chieftain and lawman - Jón Viðar Sigurðsson 1958-; Sverrir Jakobsson 1970- (The northern world: North Europe and the Baltic c. 400-1700 AD, 2017)
"Sturla Þórðarson is one of only a handful of thirteenth-century Icelandic historians to be known by name, and he is certainly one of the most significant. A number of works may be traced directly to his literary-cultural circle, notably Landnámabók (The Book of Settlements), Íslendinga saga (The saga of Icelanders) and Hákonar saga Hákonarsonar (The Saga of King Hákon). Moreover, it is thought that Sturla was involved in the production of the legal text known as Járnsíða, as well as annals and, possibly, some of the Íslendingasögur (Sagas of Icelanders). In addition to his role as author and compiler, Sturla Þórðarson was in his day one of the most powerful men in Iceland. In 1262, he visited the court of King Magnús Hákonarson ('the Law-mender') in Norway as a court poet, later becoming his liegeman, and it was for King Magnús that Sturla wrote the sagas of King Hákon and King Magnús. Sturla served as lawman of all Iceland 1272-77, and then as lawman for the north and west of the country until 1282. He died on 30 July 1284. Contributors are Ann-Marie Long, Ármann Jakobsson, Auður Magnúsdóttir, Gísli Sigurðsson, Guðrún Ása Grímsdóttir, Guðrún Nordal, Gunnar Harðarson, Hans Jacob Orning, Helgi Þorláksson, Jón Viðar Sigurðsson, Lena Rohrbach, Patricia Pires Boulhosa, Philadelphia Ricketts, R.I. Moore, Randi Bjørshol Wærdahl, Roberta Frank, Sveinbjörn Rafnsson, Sverrir Jakobsson, Theodore M. Andersson, Úlfar Bragason, and Verena Hoefig"... Provided by publisher